Diabetes mellitus mortality in a municipality in the state of São Paulo, 2010 to 2014 - Rafael Aparecido Dias Lima; Plinio Tadeu Istilli; Carla Regina de Souza Teixeira; Maria Lúcia Zanetti; Maria Tereza da Costa Gonçalves Torquato (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To describe diabetes mellitus mortality according to sex and age in a municipality in the state of São Paulo, in the period ranging from 2010 to 2014. METHODS: This was a temporal series ecological study carried out in Ribeirão Preto, state of São Paulo. The data was comprised of information on 583 deaths of Ribeirão Preto residents - regardless of the place of death - from 2010 to 2014. The data source was the electronic system of the Epidemiological Surveillance of the Municipal Health Department of the evaluated municipality. Sex, age group, premature death and year of death were chosen as variables. Subsequently, age-standardized mortality rates were calculated using the World Health Organization's standard population, in addition to total and average per death potential years of life lost. RESULTS: Mortality due to diabetes mellitus in the municipality increased during the studied period. There was a higher occurrence of female deaths, especially in the ≥ 80 years age group. The highest rates of age-standardized mortality were male. For both sexes, there was an annual mean increase of 9% in premature mortality during the studied period. Diabetes decreased life expectancy by 10 years. CONCLUSIONS: As a diagnosis of local health care, the significant increase in age-standardized mortality rates, premature mortality and potential years of life lost in the studied municipality point to the need for improvements in health promotion and disease prevention measures. It is our hope that the results presented in this study contribute to the monitoring of mortality rates in the coming years.